Investigation into the actual application of the diagnostic and therapeutic guidelines for colon cancer (Italian Journal of Public Health, 2011)
Background: In colon cancer, the effectiveness of the cure is largely dependent on the early detection of the pathology. It is therefore useful to investigate the quality prevention programs. As a result, the Italian Healthcare System is increasingly adopting Quality Assurance by implementing diagnostic and therapeutic guidelines.In this study, a comparison was made between the current pathways undertaken by patients with colon cancer and the prescribed guidelines. The analysis investigates the diagnostic pathways that lead to the discovery of colon cancer, the service center where the pathway started and the therapy regimen administered to treat the cancer.Methods: The analysis covers all 205,000 patients who accessed one Italian Local Health Agency during the year 2007. In order to fund the costs of the services, the local regional council requested the collection of data from the Agency itself. Starting from this raw data, a data warehouse was built, the required data extracted and, eventually, the actual pathways were created.Results and conclusions: Only 11.2% of colon cancer patients underwent the sequence of exams recommended by the official guidelines. 54.4% of them only partly followed the sequence of recommended exams. The remaining patients underwent exams that did not comply at all with the guidelines. Furthermore, there is evidence of a lack of prevention for some patients, particularly for those that only discovered the pathology when they arrived at the Emergency Department.
Keywords: Quality assurance; guidelines; colon cancer; cluster analysis